HUGH H. SCHWARTZ (Editor): Supply und marketing construints on hin ameritan manufacturing exports. Inter-American Development Bank-The Johns Hopkins University Press, Washington D.C. 1991 - Vega-Centeno, Máximo (1990)
La reseña no tiene resumen.